2003
DOI: 10.1021/la034370n
|View full text |Cite
|
Sign up to set email alerts
|

Microcontact Printing Using Poly(dimethylsiloxane) Stamps Hydrophilized by Poly(ethylene oxide) Silanes

Abstract: The patterning of a surface using microcontact printing (μCP) generally employs a hydrophobic micropatterned stamp made from poly(dimethylsiloxane) (PDMS) to place ink molecules on a surface with spatial control. We present a simple procedure to hydrophilize PDMS stamps based on the O2 plasma oxidation of PDMS (referred to as PDMSox) and the grafting of poly(ethylene oxide) silanes (PEO−Si) to the oxidized surface. The wetting properties of a PDMSox surface derivatized with PEO having none, one, or two silanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
163
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 68 publications
(122 reference statements)
1
163
0
Order By: Relevance
“…Ayumi ANDO, Hidetaka UNO 1) , Toshifumi ASANO 2) , Tsuneo URISU 1) and Satoshi HAMAGUCHI It is shown that neuronal model cells PC12 (rat adrenal pheochromocytoma cell line) can be cultured on a silicon (Si) substrate with the use of extracellular matrix (ECM) patterned by atmospheric-pressure plasmas (APPs). Arrangement of neuron cells in a desired pattern on a Si chip is an important step for the development of neuron cell chips.…”
Section: Arrangement Of Pc12 Cells On a Silicon Chip Via Extracellulamentioning
confidence: 99%
“…Ayumi ANDO, Hidetaka UNO 1) , Toshifumi ASANO 2) , Tsuneo URISU 1) and Satoshi HAMAGUCHI It is shown that neuronal model cells PC12 (rat adrenal pheochromocytoma cell line) can be cultured on a silicon (Si) substrate with the use of extracellular matrix (ECM) patterned by atmospheric-pressure plasmas (APPs). Arrangement of neuron cells in a desired pattern on a Si chip is an important step for the development of neuron cell chips.…”
Section: Arrangement Of Pc12 Cells On a Silicon Chip Via Extracellulamentioning
confidence: 99%
“…Layer by layer methods [21,22] result in long term stable hydrophilic coatings but involve carefully controlled multiple steps. Polyethylene oxide (PEO)-modified PDMS chips have been prepared to confer good water wettability to the microfluidic walls, but localization of these "in-bulk" treatments is not possible (and finalization of devices by sealing, i.e., with plasma, is also difficult) [23,24]. Photoinitiated grafting [25][26][27] strategies increase operational costs and become cumbersome in bonded microchannels due to non-uniformity of coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanically stable flat stamp is prepared without a photomask (since the structure may be directly written onto the surface by DPN), and the pattern drawn by DPN combined with subsequent chemical modification of the exposed areas of the stamp, allows one to create a surface with well-defined chemical regions that can be used to confine ink transport to sub-100 nm dimensions and prevent the lateral diffusion of the ink (Scheme 1). Others have used contact inking, [29,30] metal contact masks, [31,32] and template-mediated selfassembly approaches[33] to fabricate (sub)micron-sized chemical patterns on PDMS, but the approach described herein is remarkably simple and straightforward to implement and does not require complex and expensive photo-or e-beam lithography. More importantly, the high registration and resolution of DPN allow one to create stamps using this approach that ** C.A.M.…”
mentioning
confidence: 99%
“…For these experiments, either a perfluorinated silane was used to render those areas ambiphobic [32] or a PEG silane was used to make them resist the adsorption of biomolecules. [31] As an initial proof-of-concept, we prepared a flat stamp with a pattern consisting of 7×5 arrays of 1μm dots defined initially by the DPN-generated PEG features with the surrounding areas passivated with 1H,1H,2H,2H-perfluorooctadecyltrichlorosilane (PFODTS). This stamp was immersed in a 2 mM ethanolic solution of octadecanethiol (ODT), rinsed with ethanol, and then blown dry with N 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation